Comparison of the Effect of Explanatory Videos and Regatama Booklets on Adolescents' Compliance in Iron Tablet Consumption - Kirana, Indah; Farah, Naudatul; Hamid, Abdi (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to compare the effects of explanatory videos and regatama booklets on adolescents' compliance in consuming iron tablets. The problem of low compliance among adolescents in consuming iron tablets can lead to iron deficiency risks that impact health. Therefore, it is essential to investigate the most effective methods to improve compliance. The method used in this study is a quasi-experimental design with a pretest-posttest control group. The sample of this study consists of 100 adolescents, divided into two groups: one receiving explanatory videos and the other receiving regatama booklets. Data were collected through questionnaires measuring adolescents' compliance in consuming iron tablets before and after the intervention. Data analysis used a t-test to compare the two groups. The results showed that both media had a positive effect on adolescents' compliance; however, the explanatory video was more effective than the regatama booklet in increasing compliance in consuming iron tablets. This study suggests using explanatory videos as a more efficient educational method to raise awareness and improve adolescents' compliance with iron tablet consumption.